PEDAGOGICAL GAPS BETWEEN THE ACQUIRED AND DESIRED PROFICIENCY OF ENGLISH TEACHERS AT SECONDARY LEVEL - MUKHTIAR, RABIA; LODHI, MUHAMMAD ARFAN; YASMEEN, REHANA (Innovare Journal of Social Sciences, 2022)
This study helped to make teachers efficient in teaching and performance by exploring quality indicators for teaching the English language. The gap between AP and EP was identified in the present research helped teachers to work hard in low-performance areas. According to (Hughes, Granada, 2007), it is the teacher’s attitude in terms of the high level of commitment that is an important factor to affect student learning. This high level of commitment includes the teacher’s desire to keep knowledge up-to-date and self-motivation to undergo the time and again in the training process and these are the keys to success for successful teaching. In the present study, a descriptive type of research design was followed, which was quantitative in nature. The population of the study was English language teachers of secondary level government schools of district Lodhran. This study was delimited to secondary level teachers of government schools of district Lodhran. During current research questionnaire and observation were selected as data collection tools. After the collection of relevant data from SST’s, the data were analyzed through SPSS in the shape of graphs and tables to check the reliability and validity of the research. Findings from the study showed that there was a significant gap between the acquired and desired pedagogical performance. This indicates the areas which needed more hard work of the teachers to overcome the deficiencies. The government of Pakistan should take measures in terms of policy reforms that should not only improve teachers’ teaching the English language but also improve the ways of students’ learning the English language.